phân tích da thức thành nhan tử
a, a4 + 4
b, x4 + 3x2y2 + 4y4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,Sửa:a^2-b^2=\left(a-b\right)\left(a+b\right)\\ b,=a^4+2a^2b^2+b^4-2a^2b^2\\ =\left(a^2+b^2\right)^2-2a^2b^2=\left(a^2+b^2-ab\sqrt{2}\right)\left(a^2+b^2+ab\sqrt{2}\right)\\ c,=a\left(a-1\right)\\ d,=a^2-a-2a+2=\left(a-1\right)\left(a-2\right)\\ e,=a^2-2a-3a+6=\left(a-2\right)\left(a-3\right)\\ g,=a^2-3a-4a+12=\left(a-3\right)\left(a-4\right)\)
a) \(x^2-2x-4y^2-4y=\left(x^2-4y^2\right)-\left(2x+4y\right)=\left(x-2y\right)\left(x+2y\right)-2\left(x+2y\right)=\left(x+2y\right)\left(x-2y-2\right)\)
b) \(x^3+2x^2+2x+1=\left(x+1\right)\left(x^2-x+1\right)+2x\left(x+1\right)=\left(x+1\right)\left(x^2-x+1+2x\right)=\left(x+1\right)\left(x^2+x+1\right)\)
c) \(x^3-4x^2+12x-27=x^3-3x^2-x^2+3x+9x-27=x^2\left(x-3\right)-x\left(x-3\right)+9\left(x-3\right)=\left(x-3\right)\left(x^2-x+9\right)\)
d) \(a^6-a^4+2a^3+2a^2=a^2\left(a^4-a^2+2a+2\right)=a^2\left[a^2\left(a-1\right)\left(a+1\right)+2\left(a+1\right)\right]=a^2\left(a+1\right)\left(a^3-a^2+2\right)=a^2\left(a+1\right)\left[a^3+a^2-2a^2+2\right]=a^2\left(a+1\right)\left[a^2\left(a+1\right)-2\left(a-1\right)\left(a+1\right)\right]=a^2\left(a+1\right)^2\left(a^2-2a+2\right)\)
a) Ta có: \(x^2-2x-4y^2-4y\)
\(=\left(x^2-4y^2\right)-\left(2x+4y\right)\)
\(=\left(x-2y\right)\left(x+2y\right)-2\left(x+2y\right)\)
\(=\left(x+2y\right)\left(x-2y-2\right)\)
b) Ta có: \(x^3+2x^2+2x+1\)
\(=\left(x^3+1\right)+2x\left(x+1\right)\)
\(=\left(x+1\right)\left(x^2-x+1\right)+2x\left(x+1\right)\)
\(=\left(x+1\right)\left(x^2+x+1\right)\)
\(A=x^2+4=\left(x^2+4x+4\right)-4x=\left(x+2\right)^2-\sqrt{4x}=\left(x+2-\sqrt{4x}\right)\left(x+2+\sqrt{4x}\right)\)
\(B=x^4+4y^4=\left(x^4+4x^2y^2+4y^4\right)-4x^2y^2=\left(x^2+2y^2\right)^2-\left(2xy\right)^2=\left(x^2+2y^2-2xy\right)\left(x^2+2y^2+2xy\right)\)
\(a,a^4+a^2+1\)
\(=\left(a^2\right)^2+2a^2+1-a^2\)
\(=\left(a^2+1\right)^2-a^2\)
\(=\left(a^2+1-a\right)\left(a^2+1+a\right)\)
\(---\)
\(b,a^4+a^2-2\)
\(=a^4-a^2+2a^2-2\)
\(=a^2\left(a^2-1\right)+2\left(a^2-1\right)\)
\(=\left(a^2-1\right)\left(a^2+2\right)\)
\(=\left(a-1\right)\left(a+1\right)\left(a^2+2\right)\)
\(---\)
\(c,x^3-5x^2-14x\)
\(=x^3+2x^2-7x^2-14x\)
\(=x^2\left(x+2\right)-7x\left(x+2\right)\)
\(=\left(x+2\right)\left(x^2-7x\right)\)
\(=x\left(x+2\right)\left(x-7\right)\)
\(a.a^4+a^2+1\)
\(=\left(a^4+2a^2+1\right)-a^2\)
\(=\left(a^2+1\right)^2-a^2\)
\(=\left(a^2+1+a\right)\left(a^2+1-a\right)\)
\(b.a^4+a^2-2\)
\(=a^4+2a^2-a^2-2\)
\(=a^2\left(a^2+2\right)-\left(a^2-2\right)\)
\(=\left(a^2+2\right)\left(a^2-1\right)\)
\(=\left(a^2+2\right)\left(a-1\right)\left(a+1\right)\)
\(c.x^3-5x^2-14x\)
\(=x^3+2x^2-7x^2-14\)
\(=x^3\left(x+2\right)-7x\left(x+2\right)\)
\(=\left(x^3-7x\right)\left(x+2\right)\)
\(=x\left(x-7x\right)\left(x+2\right)\)
a, 2xy^2 ( x^3 -3xy - 4 )
b, x^2 - 4x - 4x +16
= x(x-4) - 4(x-4)
= (x-4) (x-4)
Câu 3:
a: 2x-8=4
nên 2x=12
hay x=6
b: 7x-3x=2x+7
\(\Leftrightarrow4x-2x=7\)
hay \(x=\dfrac{7}{2}\)
Câu 1:
a: \(5x\left(3x-4\right)=15x^2-20x\)
b: \(\left(x+5\right)\left(x-5\right)=x^2-25\)
\(x^4-27x=x\left(x^3-27\right)=x\left(x-3\right)\left(x^2+3x+9\right)\)
\(27x^5+x^2=x^2\left(27x^3+1\right)=x^2\left[\left(3x\right)^3+1^3\right]=x^2\left(3x+1\right)\left(9x^2-3x+1\right)\)
a) \(a^4+4=\left(a^4+4a^2+4\right)-4a^2=\left(a^2+2\right)^2-\left(2a\right)^2=\left(a^2+2+2a\right)\left(a^2+2-2a\right)\)
b) \(x^4+3x^2y^2+4y^4=\left(x^4+4x^2y^2+4y^4\right)-x^2y^2=\left(x^2+2y^2\right)^2-\left(xy\right)^2\)
\(=\left(x^2+2y^2+xy\right)\left(x^2+2y^2-xy\right)\)
a^4+4 àh.xem đây:(a^4+4n^2+4)-4n^2=(a^2+2)^2-(2n)^2=(a^2+2+2n)(a^2+2-2n)